First-line thrombectomy strategy for anterior large vessel occlusions: results of the prospective ETIS egistry. (10th May 2021) - Maïer, Benjamin; Finitsis, Stephanos; Bourcier, Romain; Papanagiotou, Panagiotis; Richard, Sébastien; Marnat, Gaultier; Sibon, Igor; Dargazanli, Cyril; Arquizan, Caroline; Blanc, Raphael; Piotin, Michel; Lapergue, Bertrand; et al.
Abstract : Background: The best recanalization strategy for mechanical thrombectomy (MT) remains unknown as no randomized controlled trial has simultaneously evaluated first-line stent retriever (SR) versus contact aspiration (CA) versus the combined approach (SR+CA). Objective: To compare the efficacy and safety profiles of SR, CA, and SR+CA in patients with acute ischemic stroke (AIS) treated by MT. Methods: We analyzed data of the Endovascular Treatment in Ischemic Stroke (ETIS) Registry, a prospective, multicenter, observational study of patients with AIS treated by MT. Patients with M1 and intracranial internal carotid artery (ICA) occlusions between January 2015 and March 2020 in 15 comprehensive stroke centers were included. We assessed the association of first-line strategy with favorable outcomes at 3 months (modified Rankin Scale score 0–2), successful recanalization rates (modified Thrombolysis In Cerebral Infarction (mTICI) 2b/3), and safety outcomes. Results: We included 2643 patients, 406 treated with SR, 1126 with CA, and 1111 with SR+CA. CA or SR+CA achieved more successful recanalization than SR for M1 occlusions (aOR=2.09, (95% CI 1.39 to 3.13) and aOR=1.69 (95% CI 1.12 to 2.53), respectively). For intracranial ICA, SR+CA achieved more recanalization than SR (aOR=2.52 (95% CI 1.32 to 4.81)), no differences were observed between CA and SR+CA. SR+CA was associated with lower odds of favorable outcomes compared with SR (aOR=0.63 (95% CI 0.44 to 0.90)) and CA (aOR=0.71 (95% CI 0.55 to 0.92)), higher odds of mortality at 3 months (aOR=1.56 (95% CI 1.22 to 2.0)) compared with CA, and higher odds of symptomatic intracranial hemorrhage (aOR=1.59 (95% CI 1.1 to 2.3)) compared with CA. Conclusions: Despite high recanalization rates, our results question the safety of the combined approach, which was associated with disability and mortality. Randomized controlled trials are needed to evaluate the efficacy and safety of these techniques.